SINKRONISASI KERANGKA HUKUM NASIONAL DALAM BIDANG KETENAGAKERJAAN: TINJAUAN TERHADAP UU KETENAGAKERJAAN, UU CIPTA KERJA, DAN PERATURAN PELAKSANAANNYA - Nikmah Dalimunthe; Indah Sari Br. Barus; Jahro (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
This study aims to analyze the synchronization of the national legal framework in the field of labor by examining the alignment between the Manpower Act, the Job Creation Act, and their implementing regulations. The introduction of the omnibus law brought substantial changes to labor governance, particularly regarding employment relationships, wage systems, contract flexibility, and worker protection. However, these reforms have not been fully accompanied by adequate harmonization at the level of implementing rules, resulting in inconsistencies and potential legal uncertainty. This research employs a normative legal method with statutory and comparative approaches to identify points of divergence, normative conflicts, and their implications for regulatory implementation. The findings indicate that although the Job Creation Act aims to improve regulatory efficiency and the investment climate, significant gapsremain between the primary legislation and its derivative regulations, especially in terms of worker protection and policy coherence. These results highlight the need for strengthened harmonization through regulatory evaluation, refinement of implementing rules, and alignment of legal norms to ensure a balanced relationship between economic flexibility and labor protection. The study contributes theoretically by mapping regulatory disharmony and offering analytical foundations for policymakers in shaping future labor law reforms in Indonesia.